Devulcanization of waste tire rubber using Amine Based Solvents and Ultrasonic Energy - Walvekar, Rashmi; Zulkefly, Mohammad A; Ramarad, Suganti; Siddiqui, Khalid * (2018)
This research project focuses on an alternative pathway of devulcanizing waste tire rubber by using amine based chemicals. Waste tire rubbers are known to be as toxic, non-degradable material due to their vulcanized crosslink carbon structure, and disposing of such waste could impose hazardous impacts on the environment. The current rubber recycling methods that are practiced today are rather uneconomical, nonenvironmentally friendly, and also producing recycled rubber with low quality due to the alteration in the main polymeric chains of waste rubber. This project aims to answer the question of whether the usage of amine can produce high quality rubber, where the properties of recycled rubber is almost the same as new/virgin rubber. With known potential of amine, it is a challenge for the chemical to selectively cleave the sulfur bonds without affecting the main carbon backbone chain in the rubber structure and diminishing much of the rubber properties. To study this research, aminetreated rubber must undergo devulcanisation process by applying heat and sonication energy. Then, the properties of the amine-treated rubber were determined through a set of characterization tests and analysis which are: gel content test to determine the weight of rubber before and after devulcanization, the thermogravimetric analysis (TGA) to determine the thermal degradation and stability of rubber, and Fourier Transform Infrared Spectroscopy (FTIR) to determine any structural change of the rubber. In this research so far, the first two preliminary analysis tests have been performed. The gel content test has shown that tertiary amine samples possessed a lower gel content (%) of (77 – 63 %), compared to primary amine samples (falls within the range of 80%), as well as the TGA test in which tertiary amine samples degrade faster than primary amine samples (suggesting a higher degree of rubber structure breakdown). For each type of amine, the concertation of amine did not play a major role in affecting the degree of devulcanization (as the concentration increased, the degree of devulcanization decreased for some samples). FTIR analysis showed that only sulphur-sulphur bonds were cleaved during the devulcanization process, leaving the carbon-sulphur bonds unaffected.